Diagnóstico de la fertilidad del suelo en el área de Investigación, Innovación y Desarrollo de la ESPAM - MFL. - López Párraga, Gema María (2016)
The study was conducted in CIIDEA (Center for research, innovation and agricultural development) ESPAM-MFL, whose aim was to diagnose soil fertility, by physical, chemical, parameters based on the results obtained in the laboratory on the agricultural school. The sampled experimental area was 129 ha. The altimetry survey was conducted at 1: 15.000, 40 points were taken with the drill and eight contours hole were found in the sampled area. Later, test pits were made for physical analysis were bulk density, texture, mechanical soil composition was performed. Chemical analysis of pH, organic matter, phosphorus and salinity were made. Composite samples were formed according to the methodology established Hernandez. As the results were obtained showed that the soils of the ESPAM-M.F.L, are suitable for agricultural production, showing natural fertility levels suitable for livestock farming and forestry, with the exception of phosphorus present low levels.